A pharmacogenetic determinant of mu-opioid receptor antagonist effects on alcohol reward and consumption: evidence from humanized mice - Bilbao, Ainhoa; Spanagel, Rainer; Sommer, Wolfgang H. (Biological psychiatry, 2015)
It has been proposed that therapeutic responses to naltrexone in alcoholism are moderated by variation at the mu-opioid receptor gene locus (OPRM1). This remains controversial because human results vary and no prospectively genotyped studies have been reported. We generated humanized mice carrying the respective human OPRM1 A118G alleles. Here, we used this model system to examine the role of OPRM1 A118G variation for opioid antagonist effects on alcohol responses. Effects of naltrexone on alcohol reward were examined using intracranial self-stimulation. Effects of naltrexone or nalmefene on alcohol intake were examined in continuous access home cage two-bottle free-choice drinking and operant alcohol self-administration paradigms. Alcohol lowered brain stimulation reward thresholds in 118GG mice in a manner characteristic of rewarding drugs, and this effect was blocked by naltrexone. Brain stimulation reward thresholds were unchanged by alcohol or naltrexone in 118AA mice. In the home cage, increased alcohol intake emerged in 118GG mice with increasing alcohol concentrations and was 33% higher at 17% alcohol. At this concentration, naltrexone selectively suppressed alcohol intake in 118GG animals to a level virtually identical to that of 118AA mice. No effect of naltrexone was found in the latter group. Similarly, both naltrexone and nalmefene were more effective in suppressing operant alcohol self-administration in 118GG mice. In a model that allows close experimental control, OPRM1 A118G variation robustly moderates effects of opioid antagonism on alcohol reward and consumption. These findings strongly support a personalized medicine approach to alcoholism treatment that takes into account OPRM1 genotype.